THE EFFECT OF COOPERATIVE LEARNING ON READING COMPREHENSION OF NARRATIVE TEXTS OF THE EIGHTH GRADE STUDENTS OF SMPN 13 PEKANBARU - Nelsa Desvi Edrianti; Fadly Azhar; H. Masyhur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed at finding out whether there is a significant effect of cooperative learning on reading comprehension of narrative text of the eighth grade students of SMPN 13 Pekanbaru. The research design was a pre-experimental research. The sample was VIII-2 chosen by cluster sampling technique. The result showed that the mean score of post-test (73.44) was higher than score of pre-test (63.88). The result also showed that the value of t-test (8.55) was higher than t-table (2.02) at the significance level 5%. Therefore Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. It could be concluded that there was a significant effect of cooperative learning on reading comprehension of narrative text of the eighth grade students of SMPN 13 Pekanbaru.Keywords: Cooperative Learning, Reading Comprehension, Narrative Text.